Regulation, targets and functions of CHK - Zhu, Shudong; Sun, Rong; Guo, Xialing; Bao, Yuanwu; Zhang, Dianzheng (Frontiers in Cell and Developmental Biology, 2022)
Src family kinases (SFKs) play pivotal roles in multiple signaling pathways (Yeatman et al., 2004). SFK activity is inhibited by phosphorylation at its C-terminal tyrosine, by CSK (C-terminal Src kinase) and CHK (CSK-homologous kinase). CHK expression is restricted to normal hematopoietic cells, brain, and colon tissues. Downregulation of CHK in brain and colon tumors contributes to tumorigenicity in these tissues. CHK does not phosphorylate Src efficiently, however, in contrast to CSK, CHK inhibits Src kinase activity allosterically. Although the functions of CHK are still largely unknown, potential substrates of CHK including β-synuclein, -tubulin, -spectrin, 14-3-3, and Hsp90 have been identified. CHK is regulated epigenetically via promoter methylation. As the unknown roles of CHK are beginning to be revealed, current knowledge of regulation, molecular targets and functions of CHK is summarized, and important topics for future CHK research are discussed.